Asymmetric Double‐Gate β‐Ga2O3 Nanomembrane Field‐Effect Transistor for Energy‐Efficient Power Devices. (2nd April 2019) - Ma, Jiyeon; Cho, Hyung Jun; Heo, Junseok; Kim, Sunkook; Yoo, Geonwook
Abstract: The ultra‐wide bandgap and cost‐effective melt‐growth of β‐Ga2 O3 ensure its advantages over other wide bandgap materials, and competitive electrical performance has been demonstrated in various device structures. In this paper, an asymmetric double‐gate (ADG) β‐Ga2 O3 nanomembrane field‐effect transistor (FET) comprised of a bottom‐gate (BG) metal‐oxide field‐effect transistor and a top‐gate (TG) metal‐semiconductor field‐effect transistor (MESFET) is demonstrated. Schottky contact properties are validated by characterizing the lateral Schottky barrier diode (SBD), which exhibits high rectification ratio and low ideality factor. The top‐gate β‐Ga2 O3 MESFET shows reasonable electrical performance with a high breakdown voltage, as anticipated by three terminal off‐state breakdown measurement. These properties are further enhanced by double‐gate operation, and superior device performance is demonstrated; positive‐shifted threshold voltage and reduced subthreshold slope enable the asymmetric double‐gate β‐Ga2 O3 FET to operate at low power, and almost twice as much transconductance is demonstrated for high‐frequency operation. These results show the great potential of asymmetric double‐gate β‐Ga2 O3 FETs for energy‐efficient high‐voltage and ‐frequency devices with optimal material and structure co‐designs. Abstract : An asymmetric double‐gate (ADG) β‐Ga2 O3 field‐effect transistor comprising a bottom‐gate metal‐oxide field‐effect transistor and a top‐gate metal‐semiconductor field‐effect transistor is fabricated, and exhibits significantly enhanced carrier transport properties benefiting from each individual performance modulation. The proposed structure is promising for β‐Ga2 O3 ‐based energy‐efficient high‐voltage and ‐frequency device applications.